Effects of Self-Efficacy and Survivorship Plan Enhancement Program in Acute Breast Cancer Survivors - ปะนาตา, กนกวรรณ; ศรีมรกต, ผ่องศรี; อุทริยะประสิทธิ์, เกศรินทร์; จุฑาภิสิทธิ์, สืบวงศ์ (Journal of The Royal Thai Army Nurses, 2019)
This study was quasi-experimental research with a two group pretest-posttest design aimed at assessing the effects of the self-efficacy and survivorship plan enhancement program in acute breast cancer survivors during treatment. The subjects were patients who had been diagnosed with breast cancer after surgical treatment. The subjects were monitored for post operation outcomes at Siriraj Breast Clinic, Siriraj Hospital. The first 32 subjects were purposively divided into a control group and the other 32 subjects were recruited as an experimental group. Data collection by the following tools: 1) a demographic data recording form, 2) a perceived self-efficacy questionnaire, and 3) a questionnaire on life planning for breast cancer survivors during treatment. Data were collected 2 times when patients came to the first visit after surgery and four weeks later. Data were analyzed by using descriptive statistics and variances between groups were compared with Paired t-test, Independent t-test and ANCOVA. According to the findings, posttest score of perceived self-efficacy and survival planning for acute breast cancer in the experimental group was significant higher than that of the control group (p < 0.00). Therefore, the finding from the study confirm the program should apply to acute breast cancer survivors for enhancing survivorship plan.